Welcome Guest!

# $$\S 16.2$$ Angular Momentum in Coordinate Representation

For page specific messages
For page specific messages

$\newcommand{\ket}[1]{|#1\rangle}$ $\newcommand{\bra}[1]{\langle#1|}$ $\newcommand{\norm}[1]{\langle#1|#1\rangle}$ $\newcommand{\matrixelement}[3]{\langle#1|#2|#3\rangle}$ $\newcommand{\average}[2]{\langle#1|#2|#1\rangle}$ $\newcommand{\innerproduct}[2]{\langle#1\vert#2\rangle}$ $\newcommand{\Secref}[1]{\S\ref{#1}}$ $\newcommand{\pp}[2][]{\frac{\partial#1}{\partial #2}}$ $\newcommand{\PP}[2][]{\frac{\partial^2#1}{\partial #2^2}}$ $\newcommand{\dd}[2][]{\frac{d#1}{d #2}}$ $\newcommand{\DD}[2][]{\frac{d^2#1}{d #2^2}}$ $\newcommand{\bracket}[2]{\langle #1\vert#2\rangle}$ $\newcommand{\Norm}[1]{\Vert#1\Vert}$ $\newcommand{\pair}[1]{\langle #1 \rangle}$

The orbital angular momentum of a particle is given by $\vec{L}=\vec{r}\times \vec{p}$ and the components of the angular momentum operator in coordinate representation are

\begin{eqnarray} \hat{L}_x &=& -i\hbar{\hat{y} \frac{\partial}{\partial z} - \hat{z} \frac{\partial}{\partial y} }\label{EQ01}\\ \hat{L}_y &=& -i\hbar{\hat{z} \frac{\partial}{\partial x} - \hat{x} \frac{\partial}{\partial z} }\label{EQ02}\\ \hat{L}_z &=& -i\hbar{\hat{x} \frac{\partial}{\partial y} - \hat{y} \frac{\partial}{\partial x} }\label{EQ03} \end{eqnarray}

Here $$\hat{A}$$ means operator corresponding to the dynamical variable $$A$$. In terms of  spherical polar coordinates these expressions take the form

\begin{eqnarray} \hat{L}_x &=& i\hbar \left(\sin\phi \frac{\partial}{\partial  \theta} +\cot\theta\cos\phi\frac{\partial}{\partial \phi} \right)\label{EQ04}\\ \hat{L}_x &=& i\hbar \left(\sin\phi \frac{\partial}{\partial \theta} +\cot\theta\cos\phi\frac{\partial}{\partial \phi} \right)\label{EQ05}\\ \hat{L}_z &= & i\hbar \frac{\partial }{\partial \phi}\label{EQ06} \end{eqnarray}

The operator $\vec{L}^2$ given by

$$\vec{L}^2 = \hat{L}_x^2 +\hat{L}_y^2 + \hat{L}_z^2 \label{EQ07}$$

takes the form

$$\label{EQ08} \vec{L}^2 = -\hbar^2\left[ \frac{1}{\sin\theta} \frac{\partial}{\partial\theta}\left(\sin\theta \frac{\partial}{\partial\theta} \right) + \frac{1}{\sin^2\theta}\frac{\partial^2}{\partial \phi^2} \right]$$

The components of orbital angular momentum satisfy the same commutation relations as angular momentum.

$$[L_x,L_y]= i\hbar L_z;\quad [L_y,L_z]= i\hbar L_x;\quad[L_z,L_x]= i\hbar L_y;$$

Eigenvalues and Eigenvectors

These commutation relations  of angular momentum imply that $\vec{L}^2$ commutes with $\vec{n}\cdot\hat{L}$ for all numerical$\hat{n}$. Hence we can find simultaneous eigenfunctions of $\vec{L}^2$ and a component of $\vec{L}$. along any direction $\vec{n}$. Taking $\hat{n}$ to be along $z-$ axis the eigenvalue equations

\begin{eqnarray} \vec{L}^2 Y(\theta,\phi)&=&\lambda \hbar^2 Y(\theta,\phi)\label{EQ09} \\ L_z Y(\theta,\phi)&= &\mu\hbar Y(\theta,\phi)\label{EQ10} \end{eqnarray}

become differential equations

$$\label{EQ11} \left[ \frac{1}{\sin\theta} \frac{\partial}{\partial\theta}\left(\sin\theta \frac{\partial}{\partial\theta} \right) + \frac{1}{\sin^2\theta}\frac{\partial^2}{\partial \phi^2} \right]Y(\theta,\phi) + \lambda Y(\theta,\phi)=0$$

and

$$\label{EQ12} -i\frac{\partial }{\partial \phi}Y(\theta,\phi)= \mu Y(\theta,\phi)$$

We shall now show that acceptable solutions exist only for

$$\label{EQ13} \lambda =\ell(\ell+1) ; \qquad\qquad \mu=m$$

where $\ell$ can take only positive integral values $0,1,2,\cdots$ and $m$ must satisfy

$$\label{EQ14} m= \ell,\ell-1,\cdots,-\ell+1, -\ell, \qquad \qquad ( -\ell\le m \le\ell )$$

There are $(2\ell+1)$ eigenvalues of $L_z$ for a fixed $\vec{L}^2$ and the spherical harmonics $Y_{\ell m}{\theta,\phi}$ will be seen to be the corresponding eigenfunctions. These results on eigenvalues and eigenfunctions of $\vec{L}^2$ and $L_z$ will be proved by solving the differential equations by the method of separation of variables.

Separation of Variables

To solve the differential equations we substitute

$$\label{EQ15} Y(\theta,\phi)=Q(\theta)E(\phi)$$

in Eq.\eqref{EQ11} and \eqref{EQ12} and divide by $Y(\theta,\phi)=Q(\theta)E(\phi)$. This gives

$$\label{EQ16} -i\frac{dE(\phi)}{d\phi} = \mu E(\phi)$$

Similarly, \eqref{EQ11} gives

$$\label{EQ17} \left[\frac{1}{Q(\theta)} \frac{1}{\sin\theta} \frac{\partial}{\partial\theta}\left(\sin\theta \frac{\partial}{\partial\theta} Q(\theta) \right) + \frac{1}{\sin^2\theta}\frac{1}{E(\phi)}\frac{\partial^2 E(\phi)}{\partial \phi^2} \right]+\lambda=0$$

On using Eq.\eqref{EQ16} in \eqref{EQ17} we get

$$\sin^2\theta \left\{\frac{1}{Q(\theta)} \frac{1}{\sin\theta} \frac{\partial}{\partial\theta}\left(\sin\theta \frac{\partial}{\partial\theta} Q(\theta) \right) \right\} + \lambda \sin^2\theta = - \frac{1}{E(\phi)} \frac{d^2E(\phi)}{d\phi^2}$$

While the left hand side of the above equation is a function of $\theta$, the right hand side is a function of $\phi$ alone. Hence each side must be a constant, from Eq.\eqref{EQ16}  this constant is $\mu$. Thus we get

$$\label{EQ19} \frac{1}{\sin\theta} \frac{\partial}{\partial\theta}\left(\sin\theta \frac{\partial}{\partial\theta} Q(\theta) \right) + \Big(\lambda - \frac{\mu^2}{\sin^2\theta} \Big) Q(\theta) =0$$

Solution of $$\phi$$ equation \eqref{EQ16}

General solution of Eq.\eqref{EQ16} is
$$E(\phi) = \begin{cases} A \exp(i\sqrt{\mu} \phi)+ B \exp(-i\sqrt{\mu}\phi), & \text{ if } \mu \ne 0\\ C + D \phi, & \text{ if } \mu=0 \end{cases}$$
A wave function must be single valued function. For a fixed $r,\theta, \phi$ the values of $\phi$ and $\phi+2\pi$ correspond to the same point. Hence the solution should have the same value for $\phi$ and $\phi+2\pi$. Thus we demand that $E(\phi)$ must satisfy
$$E(\phi+2\pi)= E(\phi)$$
for all $\phi$. For $$\mu=0$$ this implies that $$D=0$$.\\ Next, when $$\mu \ne 0$$ we must have
$$A \exp(i\sqrt{\mu} \phi+2\pi)+ B \exp(-i\sqrt{\mu}(\phi+2\pi))=A \exp(i\sqrt{\mu} \phi)+ B \exp(-i\sqrt{\mu}\phi)$$
or
$$\label{EQ23} A \exp(i\sqrt{\mu}\phi)\exp(2\pi)+ B \exp(-i\sqrt{\mu}\phi)\exp(2\pi))=A \exp(i\sqrt{\mu} \phi)+ B \exp(-i\sqrt{\mu}\phi).$$
For $\mu\ne 0$, the linear independence of the $\exp(\pm{i}\sqrt{\mu} \phi)$ implies that the corresponding coefficients must be equal separately giving
$$\exp(\pm{i}\sqrt{\mu}2\pi)=1 \Rightarrow \sqrt{\mu}= m,$$
where $m$ is an integer and the solutions of Eq.\eqref{EQ16} are
$$E(\phi) = \exp(i m\phi),\qquad m =0,\pm1,\pm2,\cdots$$

Solution of theta equation \eqref{EQ19}

If we substitute $w=\cos\theta$ in  Eq.\eqref{EQ19} takes the form
$$\label{EQ26} \frac{d}{dw}(1-w^2)\frac{dP(w)}{dw} +\left(\lambda -\frac{m^2}{1-w^2}\right)P(w)=0$$
where we have introduced $P(w)\equiv Q(\cos\theta)$ and have used
$$\frac{d P(w)}{d\theta} = \frac{dP(w)}{dw} \cdot \frac{dw}{d\theta}= -\sin\theta \frac{dP(w)}{dw}$$

The equation \eqref{EQ26} is known as associated Legendre equation. This equation can be solved by the method of series solution. Since \eqref{\LabelPrefix;EQ26} is a second order differential equation, there are two linearly independent solutions of this equation. For general values of $\lambda$ both the solutions become infinite at $w=\pm 1$ corresponding to $\theta=0,\pi$ These solutions are therefore unacceptable. For special values $\lambda=\ell(\ell+1)$, where $\ell$ is a positive integer, and with $|m|\le \ell$, one solution remains finite , but not the other solution. Thus we fix

$$\lambda = \ell(\ell+1) \qquad |m| \le \ell$$
For the above choice, the non singular solution for $P(w)$ is known as the associated Legendre function and  has the form

$$P^\ell_m(w) = (1-w^2)^{|m|/2} \frac{d^{|m|}}{d w^{|m|}} P_\ell(w)$$
where $P_\ell(w)$ is Legendre polynomial of degree $\ell$.Thus the eigenfunctions of $\vec{L}^2$ and $L_z$ are the
$$\label{EQ29} Y_{\ell m}(\theta,\phi) = N P^\ell_m(\cos\theta)e^{im\phi} , \qquad\qquad m=\ell,\ell-1,\cdots, \ell$$
The normalization is fixed by demanding
$$\int_0^{2\pi}d\phi \int_0^\pi Y_{\ell m}^*(\theta,\phi)Y_{\ell m}(\theta,\phi)d\theta =1$$
The functions $$Y_{\ell m}(\theta,\phi)$$ in Eq.\eqref{EQ29} are known as spherical harmonics.

n